СРАВНИТЕЛЬНАЯ ХАРАКТЕРИСТИКА ВНУТРЕННЕЙ СТРУКТУРЫ ВЕГЕТАТИВНЫХ ОРГАНОВ ДВУХ ВИДОВ РОДА Berberis tarr. Et Gray. В РАЗНЫХ ЭКОЛОГИЧЕСКИХ УСЛОВИЯХ АЛМАТИНСКОЙ ОБЛАСТИ (Experimental biology, 2015)
It is presented Results of the study of an anatomic structure of annual stems of Berberis sphaerocarpa Kar. et Kir and Berberis iliensis M. Pop. in this article.
Keywords: anatomic structure